2015
DOI: 10.1103/physrevc.91.024326
|View full text |Cite
|
Sign up to set email alerts
|

Electron-scattering form factors forLi6in theab initiosymmetry-guided framework

Abstract: We present an ab initio symmetry-adapted no-core shell-model description for 6 Li. We study the structure of the ground state of 6 Li and the impact of the symmetry-guided space selection on the charge density components for this state in momentum space, including the effect of higher shells. We accomplish this by investigating the electron scattering charge form factor for momentum transfers up to q ∼ 4 fm −1 . We demonstrate that this symmetry-adapted framework can achieve significantly reduced dimensions fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…This remains valid for various Ω values, as well as when different bare interactions are employed. Deviations in the form factor (and in the one-body densities) as a result of the SU(3)-based selection of model spaces are found to be only marginal and to decrease for higher Ω [87].…”
Section: Electron Scattering For Light Nucleimentioning
confidence: 99%
See 3 more Smart Citations
“…This remains valid for various Ω values, as well as when different bare interactions are employed. Deviations in the form factor (and in the one-body densities) as a result of the SU(3)-based selection of model spaces are found to be only marginal and to decrease for higher Ω [87].…”
Section: Electron Scattering For Light Nucleimentioning
confidence: 99%
“…3 of Ref. [87]). We note that the N max = 12 results continue to deviate from the experimental data for intermediate momenta, especially for q 2 fm −1 , where two-body currents become significant for C0 as shown by the Variational Monte Carlo (VMC) [6] with the AV18 [1] two-nucleon and Urbana IX [266] three-nucleon interactions.…”
Section: Electron Scattering For Light Nucleimentioning
confidence: 99%
See 2 more Smart Citations
“…The concept underpinning the SA-NCSM has been demonstrated in our recent ab initio studies of properties of 6 Li, 6 He, and 8 Be [18,33]. The potential gains from the SA-NCSM have also been demonstrated in our earlier study where we found that ab initio wavefunctions of 12 C and 16 O calculated by the no-core shell model (NCSM) [4] project well onto a symmetry-adapted subspace that is only a tiny fraction of the corresponding complete model space [34][35][36].…”
Section: Introductionmentioning
confidence: 99%